Manfaat dan Tantangan Regulasi Penyelenggaraan Financial Technology (Fintech) di Indonesia - Masduqie, Muhammad Hamdan Ali; Santoso, Tulus Budi (Institut Agama Islam YPBWI Surabaya, 2023)
Abstract: The development of financial technology (fintech) that occurs globally has given challenges to the financial services sector. Regulatory challenges are mainly due to the decentralization of the financial system as a result of implementing fintech. The problems studied in this study include: (1) What are the implications of the development of fintech and the phenomenon of decentralization of the financial system on the regulatory challenges faced in Indonesia. (2) What form of regulation can be applied in Indonesia to address the challenges of fintech development and decentralization of the financial system. The decentralization of the financial system caused by the implementation of fintech has given rise to its own regulatory challenges. The absence of a comprehensive fintech regulation capable of accommodating the phenomenon of financial system decentralization has the potential to result in weak guarantees of legal certainty and protection. The preparation of the fintech Law based on a principle approach can be a solution to answer the regulatory challenges faced. This paper is juridical normative legal research with conceptual approach, statutory and comparative approach. Keywords: Financial Technology, Decentralized Financial System, Regulation.